An asymmetric dynamic struggle between pirates and producers - Alex Coram (University of Massachusetts, Department of Economics, 2006)
The purpose of this paper is to contribute to our understanding of the dynamics of struggles over resources by studying a game between a producer that can guard and buy fortifications and a pirate. It is assumed that the returns from defence and raiding depends on the ratio of the resources spent on each activity and that all produced goods can be stolen. It attempts to characterise the trajectory of the resources and the defence and raiding activities of the pirate and producer. I show, among other things, that the pirate's strategy is to farm the producer and that the pirate's raiding activities and resources will decline as the productive capacity of the producer increases. I also show that a flexible guarding strategy may be preferred to fixed fortifications if the producer's resources are low at any time.
Keywords: C61; C72; P14; D00; 330; resource struggles; piracy; differential games; optimal control